Determination of the Intensive Care Nurses’ Attitudes towards Evidence-Based Practices - Söylemez, Nilgün; Güneş, Dilek (Ordu Üniversitesi, 2024)
Objective: This research was carried out to determine the attitudes of intensive care nurses towards evidence-based nursing. Methods: This descriptive study was conducted with 134 nurses working in the intensive care units of a university hospital between January and June 2021. Research data were collected by online data collection technique using “Descriptive Form for Nurses” and “Evidence-Based Nursing Attitude Questionnaire (EBNAQ)”. The obtained data were analyzed by using descriptive statistics (number, percentage, mean) and Mann Whitney U tests in the computer-aided SPSS package program. Results: It was determined that the intensive care nurses’ mean total score in the Evidence-Based Nursing Attitude Questionnaire (EBNAQ)was 66.35±6.22. Evidence-Based Practice Intentions Subscale was found to be higher in female nurses than in male nurses (p
Keywords: ICU Nursing; Yoğun Bakım Hemşireliği